Chemical composition and cardiovascular effects induced by the essential oil of Cymbopogon citratus DC. Stapf, Poaceae, in rats - Moreira, Flávia Viana (2010)
C. citratus é utilizada na medicina popular para tratar hipertensão. Este trabalho investigou a composição química e os efeitos cardiovasculares do óleo essencial do C. citratus (OECC). Foram identificados oito constituintes no OECC, sendo geranial o majoritário (43,08%). Em ratos, o OECC (1, 5, 10 e 20 mg/kg, i.v.) induziu hipotensão e bradicardia que foram atenuadas pela atropina e tiopental sódico, mas não por L-NAME ou indometacina. Em anéis de artéria mesentérica de ratos pré-contraídos com fenilefrina, o OECC (1 a 3000 µg/mL) induziu relaxamento que não foi afetado após remoção do endotélio, após TEA ou em anéis pré- contraídos com KCl (80 mM). Além disso, o OECC (1000 µg/mL) não induziu efeito adicional sobre o relaxamento máximo da nifedipina (10 µM). Em conclusão, o OECC induz hipotensão possivelmente devido à redução da resistência vascular que pode ser causada por inibição do influxo de Ca2+, e bradicardia provavelmente devido à ativação de receptores muscarínicos cardíacos._________________________________________________________________________________________ ABSTRACT: Cymbopogon citratus DC. Stapf, Poaceae, is used in the folk medicine for hypertension treatment. This work investigated the chemical composition and cardiovascular effects in rats of C. citratus essential oil (EOCC). A phytochemical screening demonstrated the presence of eight constituents, being geranial the major compound (43.08%). In rats, EOCC (1, 5, 10, and 20 mg/kg, i.v.) induced transient hypotension and bradycardia that were attenuated by atropine and sodium thiopental, but not by L-NAME or indomethacin. In rings of rat superior mesenteric artery pre-contracted with phenylephrine, EOCC (1 to 3000 µg/mL) induced relaxation that was not affected after removal of the endothelium, after TEA or in rings pre-contracted with KCl (80 mM). Furthermore, EOCC (1000 µg/mL) was not able to induce additional effect on maximal relaxation of nifedipine (10 µM). In conclusions, EOCC induces hypotension, possibly by reduction in vascular resistance caused by inhibition of the Ca2+ influx, and bradycardia probably due to an activation of cardiac muscarinic receptors.